Dynamics of Body Image Formation in Female Celebrities - Bernadette Btari Kania Putri; Retno Hanggarani Ninin (Daengku: Journal of Humanities and Social Sciences Innovation, 2023)
In this modern era, social media, especially Instagram, has formed a new celebrity population called "Selebgram," where the audience recognizes, admires, and follows their identities and lives. In Instagram, the communication between "Selebgram" and followers is through likes and comments. Several studies have been conducted on this communication system, and it has been found that likes and comments give rise to excessive social comparison and self-objectification, which can lead to an unrealistic idealization of body image and body image dissatisfaction. Such dissatisfaction then results in psychological disorders such as poor self- and body-esteem, unstable mood, stress, anxiety, and eating disorders, especially among teenage girls. Teen girl "selebgrammers" with high engagement on social media are thought to show a more complex body image idealization dynamic that will be examined in this qualitative study. Through interviews or online questionnaires, this study was conducted on six girl micro-celebrities in their teens in Indonesia. The results showed that the dynamics of body image idealization among girls on "Selebgram" consist of four steps: (1) internalization of the ideal media; (2) self-objectification and social comparison; (3) body image dissatisfaction, moderated by significant others, the purpose of using Instagram, and religion; and (4) self-branding containing self-presentation.